Cynaroside inhibits Leishmania donovani UDP-galactopyranose mutase and induces reactive oxygen species to exert antileishmanial response. Issue 1 (29th January 2021) - Tabrez, Shams; Rahman, Fazlur; Ali, Rahat; Alouffi, Abdulaziz S.; Akand, Sajjadul Kadir; Alshehri, Bader Mohammed; Alshammari, Fahdah Ayed; Alam, Aftab; Alaidarous, Mohammed A.; Banawas, Saeed; Dukhyil, Abdul Aziz Bin; Rub, Abdur
Abstract: Cynaroside, a flavonoid, has been shown to have antibacterial, antifungal and anticancer activities. Here, we evaluated its antileishmanial properties and its mechanism of action through different in silico and in vitro assays. Cynaroside exhibited antileishmanial activity in time- and dose-dependent manner with 50% of inhibitory concentration (IC50 ) value of 49.49 ± 3.515 µM in vitro . It inhibited the growth of parasite significantly at only 20 µM concentration when used in combination with miltefosine, a standard drug which has very high toxicity. It also inhibited the intra-macrophagic parasite significantly at low doses when used in combination with miltefosine. It showed less toxicity than the existing antileishmanial drug, miltefosine at similar doses. Propidium iodide staining showed that cynaroside inhibited the parasites in G0 /G1 phase of cell cycle. 2, 7-dichloro dihydro fluorescein diacetate (H2 DCFDA) staining showed cynaroside induced antileishmanial activity through reactive oxygen species (ROS) generation in parasites. Molecular-docking studies with key drug targets of Leishmania donovani showed significant inhibition. Out of these targets, cynaroside showed strongest affinity with uridine diphosphate (UDP)-galactopyranose mutase with −10.4 kcal/mol which was further validated by molecular dynamics (MD) simulation. The bioactivity, ADMET (absorption, distribution, metabolism, excretion and toxicity) properties, Organisation for Economic Co-operation and Development (OECD) chemical classification and toxicity risk prediction showed cynaroside as an enzyme inhibitor having sufficient solubility and non-toxic properties. In conclusion, cynaroside may be used alone or in combination with existing drug, miltefosine to control leishmaniasis with less cytotoxicity.